2019
DOI: 10.1530/ec-19-0372
|View full text |Cite
|
Sign up to set email alerts
|

Large cell neuroendocrine carcinoma with a solitary brain metastasis and low Ki-67: a unique subtype

Abstract: IntroductionStage IV large cell neuroendocrine carcinoma (LCNEC) of the lung generally presents as disseminated and aggressive disease with a Ki-67 proliferation index (PI) 40–80%. LCNEC can be subdivided in two main subtypes: the first harboring TP53/RB1 mutations (small-cell lung carcinoma (SCLC)-like), the second with mutations in TP53 and STK11/KEAP1 (non-small-cell lung carcinoma (NSCLC)-like). Here we evaluated 11 LCNEC patients with only a solitary brain metastasis and evaluate phenotype, genotype and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The eight studies finally selected were all retrospective studies [ 6 , 9 , 10 , 18 , 19 , 20 , 21 , 22 ] including a total of 268 patients with NECs in which Ki67 LI was specified to distinguish two subcategories: NECs with Ki67 LI <55% and NECs with Ki67 LI ≥55% ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The eight studies finally selected were all retrospective studies [ 6 , 9 , 10 , 18 , 19 , 20 , 21 , 22 ] including a total of 268 patients with NECs in which Ki67 LI was specified to distinguish two subcategories: NECs with Ki67 LI <55% and NECs with Ki67 LI ≥55% ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies differed according to types of NEN enrolled and treatments received. Specifically, four studies considered both WD G3 NENs and PD-NENs [ 6 , 19 , 21 , 22 ], while four studies [ 9 , 10 , 18 , 20 ] included only patients presenting the specific subgroup of NECs. NENs derived from different primary sites, the most frequent one being the GEP tract.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A significant difference in OS (Figure 7), but not in DFS, was observed using ≥25 as the mitotic rate cut‐point (log‐rank P = 0.032), while no significant correlation with OS or DFS was observed using ≥20 or ≥30 as the mitotic rate cut‐point (log‐rank P = 0.47 and P = 0.24, respectively). The systematic review of the literature identified 14 original papers that evaluated ≥10 LCNEC without comingling the results for LCNEC and SCLC 6,9,13,21,42–51 . As shown in Table 1, these reports provided varied incomplete information regarding the method/protocol utilised and/or number of tumour cells assessed to determine Ki‐67%.…”
Section: Resultsmentioning
confidence: 99%